Tourism border-making: A political economy of China's border tourism - Jennifer Cave (Annals of Tourism Research, 2019)
This paper is the result of 4 years of research which identifies evolutionary processes and developmental impacts upon communities and tourism business within changing power structures at the Chinese/ Myanmar border. The significant contribution it makes to literature is identification of agency contained within tourism development as a force which (de)constructs conceptions of borders between nations but paradoxically is contained in ‘official’ place-making narratives.